2020
DOI: 10.1080/20548923.2020.1738728
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to identify ancient wine production using biomolecular approaches?

Abstract: Chemical analysis of archaeological artefacts is used with increasing regularity to understand how wine was produced, traded, and consumed in the past and to shed light on its antiquity. Based both on an extensive review of the published literature and on new analyses, here we critically evaluate the diverse range of methodological approaches that have been used for wine identification. Overall, we conclude that currently none of the proposed chemical 'biomarkers' for wine provide unequivocal evidence. Neverth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 70 publications
1
46
0
1
Order By: Relevance
“…Comparison of the proportions of malic and tartaric acids in the pots was used to distinguish between the presence of grapevine products and that of other plants ( Fig 7 ) [ 17 , 85 – 88 ] ( S3 Text ). Four vessels from CLESP and one sample from CSP produced a ratio of tartaric acid to the sum of tartaric and malic acids (%TA) of greater than 35%, characteristic of ripe grapes and their products (wine, juice, vinegar), as well as tamarind and some pomegranate cultivars [ 17 , 85 ] ( Fig 7B ). Indeed, studies have suggested that cooking wares may have been used for the storage or heating of wine as well as being used as a flavouring for food in medieval Florence and Piombino [ 89 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparison of the proportions of malic and tartaric acids in the pots was used to distinguish between the presence of grapevine products and that of other plants ( Fig 7 ) [ 17 , 85 – 88 ] ( S3 Text ). Four vessels from CLESP and one sample from CSP produced a ratio of tartaric acid to the sum of tartaric and malic acids (%TA) of greater than 35%, characteristic of ripe grapes and their products (wine, juice, vinegar), as well as tamarind and some pomegranate cultivars [ 17 , 85 ] ( Fig 7B ). Indeed, studies have suggested that cooking wares may have been used for the storage or heating of wine as well as being used as a flavouring for food in medieval Florence and Piombino [ 89 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Small organic acids, which are relatively insoluble in organic solvents were extracted from > 50% of the samples, using an acid butylation extraction developed by Garnier and Valamoti (2016) [17,29,85]. Malic and tartaric acids were identified, in variable amounts, in 97% and 70% of them, respectively.…”
Section: Evidence Of Vegetables Fruits and Cerealsmentioning
confidence: 99%
See 3 more Smart Citations